Virtual reference best practices tailoring services to your library - Kern, M. Kathleen (IG library, 2009)
When it comes to virtual reference, one size doesn't fit all. What works in one library won't necessarily work in another. How do you figure out what to do? The recently published Virtual Reference Service Guidelines from the Reference and User Services Association (RUSA), which is reproduced in appendix A, provides the starting point. Kern, a leading virtual reference expert, outlines the tools and decision-making processes that will help you and your library evaluate, tailor, and launch virtual reference services that are a perfect fit for your community and your library.